2007
DOI: 10.1073/pnas.0606636104
|View full text |Cite
|
Sign up to set email alerts
|

The optimal height of the synaptic cleft

Abstract: Signal integration in the brain is determined by the size and kinetics of rapid synaptic responses. The latter, in turn, depends on the concentration profile of neurotransmitter in the synaptic cleft. According to a traditional view, narrower clefts should correspond to higher intracleft concentrations of neurotransmitter, and therefore to the enhanced activation of synaptic receptors. Here, we argue that narrowing the cleft also increases electrical resistance of the intracleft medium and therefore reduces lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(200 citation statements)
references
References 40 publications
8
183
0
9
Order By: Relevance
“…The cleft between membranes at the synapse is ∼15-25 nm, which is similar to that of the pSJ cleft and considered optimal for synaptic function (Savtchenko and Rusakov, 2007). Transmission EM of the well-characterized synapses at the Drosophila neuromuscular junction (NMJ) reveals the presence of regularly spaced electron-dense material in cross section and a honeycomb-like appearance in oblique sections, which both are similar in appearance to the pSJ (Prokop, 1999).…”
Section: The Septate Junction and Its Originsmentioning
confidence: 73%
“…The cleft between membranes at the synapse is ∼15-25 nm, which is similar to that of the pSJ cleft and considered optimal for synaptic function (Savtchenko and Rusakov, 2007). Transmission EM of the well-characterized synapses at the Drosophila neuromuscular junction (NMJ) reveals the presence of regularly spaced electron-dense material in cross section and a honeycomb-like appearance in oblique sections, which both are similar in appearance to the pSJ (Prokop, 1999).…”
Section: The Septate Junction and Its Originsmentioning
confidence: 73%
“…Our evidence therefore indicates that the most proximal AIS segment serves as a resistive spacer element that ensures proper isolation of the distally located trigger zone from the immense somatodendritic electrical load. At any realistic axoplasm resistivity values [which we assumed to be higher than 80 Ω·cm, the artificial cerebrospinal fluid (ACSF) resistivity (25)], AIS relocation further down the axon would not, by itself, be the reason for a decrease in neuronal excitability (24).…”
Section: Resultsmentioning
confidence: 99%
“…Such cleft width has been estimated by carefully calibrated studies and remains relatively constant in many synapses (Peters et al, 1991, Zuber et al, 2005. Moreover, a recent theoretical study has suggested that such width would be optimal for efficient synaptic transmission (Savtchenko and Rusakov, 2007). In contrast to most synaptic contacts in the CNS, RG and CG axon terminals extend well over the IMP cluster area at relay cells because these synapses are formed directly on the dendritic shaft.…”
Section: Sds-frlmentioning
confidence: 99%